A Case Report Of Polyarticular Septic Arthritis With Distal Tibia And Fibula Chronic Osteomyelitis Treated With Empirical Antibiotics And Wound Debridement (Journal of Pharmaceutical Negative Results, 2023)
Septic arthritis with osteomyelitis is rare case but emergency medical condition which needs immediate intervention1 to 2. Most commonly seen in knee joint but can also occur in ankle joint. Patient usually presents acutely with pain, swelling, fever, restriction of movements at affected joint. Diagnosis is made on clinical examination and radiological investigation. Comorbidities is a major concern in septic arthritis cases due to adverse effects which includes localized joint destruction and systemic consequences like septicemia, organ failure and death2 to 4. Condition is treated with empirical antibiotic coverage for weeks with wound debridement. If not treated in adequate time it leads to future amputation and even death due to septicemia2 to 4.